Late Contralateral Recurrence of Unilateral Acute Idiopathic Maculopathy: Adaptive Optics Findings. (3rd April 2022) - Faure, Céline; Cognard, Pauline; Robert, Matthieu P.
ABSTRACT: Purpose: To report a case of late contralateral recurrence of unilateral acute idiopathic maculopathy (UAIM) and its sequelae by using adaptive optics. Methods: A 46-year-old woman positive for coxsackie virus presented with a typical UAIM, followed 3 years later by a recurrence in the fellow eye. At an early stage, spectral domain-OCT showed a localized loss of the inner segment/outer segment and cone outer segment tips lines, while flood-illumination adaptive optics displayed pigment clumpings and transient small hard exudates, associated with a persistent blurring of the cone mosaic. Results: These findings support the hypothesis of an outer retinal blood-barrier breakdown, inducing a disruption limited to the outer segment of the photoreceptors, followed by a progressive though incomplete normalization of the cone mosaic characterized by a persistent misalignment of outer segment tips. Conclusion: This would explain the acute clinical presentation of UAIM, followed by a spontaneous, partial, recovery, with a relative scotoma remaining over time.